Digital Marketing Content and Purchase Decisions: The Mediating Role of Brand Awareness in the Indonesian Coffee Shop Industry - Edwin Novelino Wonkay; Ni Kadek Suryani; Anita Heptariza (Journal of Social Work and Science Education, 2027)
The increasing reliance on digital marketing has transformed how coffee shop businesses communicate with consumers, yet the mechanism through which digital marketing content influences purchase decisions remains insufficiently understood, particularly through the mediating role of brand awareness. This study examines the influence of digital marketing content on purchase decisions through brand awareness among Janji Jiwa consumers in East Denpasar. A quantitative research design was employed using a survey of 100 consumers selected through purposive sampling. Data were collected using structured questionnaires and analyzed through path analysis and the Sobel test with SPSS. The findings demonstrate that digital marketing content significantly enhances brand awareness, while both digital marketing content and brand awareness positively influence purchase decisions. Moreover, brand awareness significantly mediates the relationship between digital marketing content and purchase decisions, indicating that consumers’ purchasing behaviour is shaped not only by direct exposure to digital content but also by the extent to which such content strengthens brand recognition and recall. The novelty of this study lies in integrating digital marketing content, brand awareness, and purchase decisions within a single mediation framework in the context of Indonesia’s coffee shop industry. The findings contribute to digital marketing literature by clarifying the psychological mechanism linking content marketing to consumer purchasing behaviour and provide practical insights for coffee shop managers in designing engaging digital content strategies that strengthen brand awareness and encourage sustainable purchase decisions.